Engineering Warms to Frozen Light. - Sweet, W.
As the last cofferdam holding the waters of China's Yangtze River was blown up in a series of blasts over a 12-second period on June 6, 2006, the 2.5-km wide dam now holds the full force of the river and is ready to ramp up to its total rated electrical capacity of 22,400 megawatts. The caps of the fourteen 700-MW turbines in the generator room of the dam's left bank are now in full operation, and another 18 turbines are set to be installed in a similar room on the dam's right bank. Despite controversy surrounding the project's environmental, social and economic implications, many are optimistic that it will fulfil its prodigious promise
Keywords: 2.5 km; 22400 MW; 700 MW; China; Three Gorges dam; Yangtze River; Dam; Hydroelectric power stations; Total rated electrical capacity; Turbines